2022
DOI: 10.1182/bloodadvances.2021004958
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vitamin D level at diagnosis and transplantation on the prognosis of hematological malignancy: a meta-analysis

Abstract: Vitamin D deficiency impairs prognosis in many types of cancer; however, its significance in each subtype of hematological malignancies is unclear. In addition, data on the association between pre-transplant vitamin D levels and outcomes of hematopoietic stem cell transplantation (HSCT) are inconsistent. This systematic review and meta-analysis aimed to elucidate the impact of vitamin D levels at diagnosis or pre-HSCT on the prognosis of hematological malignancies. A total of 30 articles and abstracts were ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 85 publications
1
13
0
Order By: Relevance
“…Concordantly with the association between low vitamin D status and poorer overall survival and progression-free survival in myeloid and lymphoid malignancies [ 161 ], in several types of leukemic cells, 1,25-(OH) 2 D 3 regulates essential pathways for survival and proliferation such as TLR, STAT1/3 or PI3K/AKT that are induced by immune cell–cell or cytokine activation [ 162 , 163 ].…”
Section: Mechanisms Introductionmentioning
confidence: 95%
“…Concordantly with the association between low vitamin D status and poorer overall survival and progression-free survival in myeloid and lymphoid malignancies [ 161 ], in several types of leukemic cells, 1,25-(OH) 2 D 3 regulates essential pathways for survival and proliferation such as TLR, STAT1/3 or PI3K/AKT that are induced by immune cell–cell or cytokine activation [ 162 , 163 ].…”
Section: Mechanisms Introductionmentioning
confidence: 95%
“…There was a study showing vitamin D deficiency in NDMM is unrelated to survival or cytogenetics ( 12 ). Contrary to this, another clinical observation found that vitamin D deficiency corelated to poor overall survival in white NDMM patients, rather than African American patients, implying vitamin D status and its clinical relevance in MM are strongly influenced by racial differences ( 9 , 12 ) 。 As vitamin D signaling has a key regulatory role in maintaining a healthy immune system, controlling cell proliferation, differentiation and growth, and inhibiting angiogenesis ( 8 ), keep clarifying the significance of vitamin D deficiency in myeloma development is undoubtedly needed.…”
Section: Introductionmentioning
confidence: 99%
“…Recent clinical studies have revealed a consistent and strong association between vitamin D status and tumor progression and survival in several solid tumor ( 7 ). Vitamin D deficiency is extremely common in patients with multiple myeloma (MM), however, data on the association between vitamin D status and clinical outcomes of newly diagnosed multiple myeloma (NDMM) are rather inconsistent ( 8 12 ). There was a study showing vitamin D deficiency in NDMM is unrelated to survival or cytogenetics ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis, Ito et al [178] observed that lower vitamin D levels were associated with significantly poorer overall survival (HR: 1.50, 95%CI 1.03-2.18) and a higher relapse rate (HR: 2.12, 95%CI 1.41-3.19), while no significant impact on non-relapse mortality (NRM) was described (HR: 1.23, 95%CI 0.72-2.10).…”
Section: Vitamin D Levels: Impact On Allogenic Hsct Outcomesmentioning
confidence: 99%